Pattern of Inappropriate use of Topical Corticosteroid and Cutaneous Adverse Effects at a Tertiary Level Hospital in Kathmandu - Sabina Bhandari; Upama Paudel (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: Topical corticosteroids are anti-inflammatory, immunosuppressive, and anti-proliferative drugs with profound efficacy. As it provides rapid relief, it is used for  a wide spectrum of dermatological conditions. Rampant use of topical corticosteroids due to their  easy availability gives rise to difficult-to-treat cutaneous adverse effects.